Kecubung Intoxication: A Case Report on A 16-Year-Old Male at Kuningan District - Saputera, Monica Djaja; Saputera, Jessica Djaja (UI Scholars Hub, 2022)
Kecubung (angel’s trumpet) is a plant with hallucinogen effect which contain a tropane alkaloid, which are widely grown in Indonesia and is widely abused by several groups of adolescents aged 18 years in East Nusa Tenggara. Kecubung intoxication is a common case in Indonesia, but rarely reported and hard to make a definitive diagnosis due to lack of the toxicology screening assessment. Besides, an antidote of this case also not available in this country. We present a case of 16-years old male who visited the emergency room with fluctuating level of consciousness accompanied by anxiety, anger, and a visual hallucination. He was given an IV Diazepam 10 mg and Alprazolam 0.5 mg oral in the first day, and continue with Risperidone 2 mg oral – twice a day, Trihexyphenidyl Hydrochloride 2 mg and Clozapine 12.5 mg oral – once a day, and resulting in significant improvement of symptoms and behavior.